Adjuvant radiotherapy after prostatectomy for prostate cancer in Japan: a multi-institutional survey study of the JROSG - Aoki, Manabu (Oxford University Press, 2014)
In Japan, the use of adjuvant radiotherapy after prostatectomy for prostate cancer has not increased compared with the use of salvage radiotherapy. We retrospectively evaluated the outcome of adjuvant radiotherapy together with prognostic factors of outcome in Japan. Between 2005 and 2007, a total of 87 patients were referred for adjuvant radiotherapy in 23 institutions [median age: 64 years (54–77 years), median initial prostate-specific antigen: 11.0 ng/ml (2.9–284 ng/ml), Gleason score (GS): 6, 7, 8, 9, 10 = 13.8, 35.6, 23.0, 27.6, 0%, respectively]. Rates of positive marginal status, seminal vesicle invasion (SVI) and extra-prostatic extension (EPE) were 74%, 26% and 64%, respectively. Median post-operative PSA nadir: 0.167 ng/ml (0–2.51 ng/ml). Median time from surgery to radiotherapy was 3 months (1–6 months). A total dose of ≥60 Gy and <65 Gy was administered to 69% of patients. The median follow-up time was 62 months. The 3- and 5-year biochemical relapse-free survival (bRFS) rates for all patients were 66.5% and 57.1%, respectively. The GS and marginal status (P = 0.019), GS and SVI (P = 0.001), marginal status and EPE (P = 0.017), type of hormonal therapy and total dose (P = 0.026) were significantly related. The 5-year bRFS rate was significantly higher in SVI-negative patients than SVI-positive patients (P = 0.001), and significantly higher in patients with post-operative PSA nadir ≤0.2 than in patients with post-operative PSA nadir >0.2 (P = 0.02), and tended to be more favorable after radiotherapy ≤3 months from surgery than >3 months from surgery (P = 0.069). Multivariate analysis identified SVI and post-operative PSA nadir as independent prognostic factors for bRFS (P = 0.001 and 0.018, respectively).